Questionnaire for detecting professional burnout syndrome: development and validation of a new diagnostic method - Chaban, Олег; Khaustova, Олена; Omelyanovich, Віталій (Psychosomatic Medicine and General Practice, 2025)
Introduction. Despite the large number of English-language diagnostic scales and questionnaires aimed at studying burnout, as well as the presence of Ukrainian versions of these tests in a number of publications, as a result of a bibliographic study, it was found that at present all Ukrainian versions of the questionnaires are machine translations from Russian and none of them has undergone validation procedures on a Ukrainian sample. This indicates the relevance of the development and validation of the first Ukrainian questionnaire for diagnosing burnout. The aim of the study was to create a new scale for diagnosing burnout syndrome and confirm the acceptability of its psychometric characteristics. The study was carried out within the framework of the research of the Department of Medical Psychology, Psychosomatic Medicine and Psychotherapy of the O. O. Bogomolets National Medical University (state registration number 0122U202016). Research material and methods. The study material was the results of a survey using the developed questionnaire of 1405 scientific and pedagogical workers of higher educational institutions of Ukraine. The validation of the test was carried out using exploratory factor analysis, calculation of Spearman's rank correlation coefficient, coefficient δ - L. Ferguson, coefficient α -L. Cronbach; Guttman's bisection coefficient; Spearman-Brown's equivalent forms coefficient. Research results and their discussion. As a result of calculating the criterion validity by conducting factor analysis, 10 factors were obtained, after which the first version of the questionnaire was reduced to 10 questions that had the lowest factor loadings. Thus, the questionnaire consists of 50 questions with a dichotomous response scale, the evaluation of the answers to which is based on the principle of dimensionality for the formation and/or manifestation of burnout syndrome. Determination of the discriminativeness of the questionnaire was carried out by calculating the coefficient δ - L. Ferguson and indicated its extremely high level (δ-Ferguson=0.988). The indicators that assess the consistency of the questionnaire during statistical analysis also turned out to be very high: α-Cronbach = 0.877; Guttman split-half = 0.848; Equal-length Spearman – Brown = 0.857. The synchronous reliability of the questionnaire was assessed using the results of Spearman correlation analysis, as a result of which it was found that most of the questionnaire items have statistically significant positive correlations with the integral test indicator ( ≥ 0.419; p ≤ 3.29E-15). Conclusions. All of the above indicates the possibility of using the first Ukrainian “Questionnaire for identifying professional burnout syndrome” (© Chaban O.S., 2025) in practical psychology, medicine and scientific research on burnout.